The High school chemistry tutor - Fogiel, M., (Max); Research and Education Association (Piscataway, N.J. : The Association, 1991)
A study guide to chemistry for high school students that includes practice problems with detailed explanations on how to get the answers.
Includes index.
Rev. ed. of: The High school chemistry problem solver. c1986.
Young Adult
Keywords: Chemistry -- Problems, exercises, etc; Chemistry -- Study and teaching (Secondary); Chemistry -- Problems, exercises, etc; Chemistry -- Study and teaching